Investigating nurses’ quality of life and work-life balance statuses in Singapore - Kowitlawkul, Y.; Yap, Suk Foon; Makabe, Sachiko; Chan, S.; Takagai, Junko; Tam, Wilson Wai San; Nurumal, Mohd Said (Blackwell Publishing Ltd, 2019)
tertiary hospital in Singapore. Background: Nurses’ quality of life can directly and indirectly impact patients’ safety and quality of care. Therefore, identifying key factors that influence nurses’ quality of life is essential in the healthcare delivery system. Methods: A descriptive quantitative study design was adopted, and validated questionnaires were used. Data were collected in a period of 3 months (March to May 2014) at a 600-bed tertiary hospital in Singapore. One thousand and forty nurses participated in the study. Results: Social support and sense of coherence were found to be significant predictors for high quality of life in all domains. Most nurses in this study spent more time on work than their private lives. However, there was no significant difference in job satisfaction among the four groups of nurses’ proportions of percentages of actual time spent on work and private life. Conclusions: Cultivating social support from family, friends/colleagues and supervisors can help an individual cope with stress and enhance a nurse’s quality of life. Implications for nursing policy and practice: Even though nurses who spent more time at work were still satisfied with their job, they might need to be aware of their physical health and work environment. Nursing policy related to nurses’ physical health and environment should be established. Health promotion programmes such as physical exercise and mindfulness interventions should be conducted to promote nurses’ well-being and healthy workplace environments to enhance nurses’ quality of life.